Histopathological correlation of abnormal uterine bleeding in perimenopausal women - Byna, Prasanna; Siddula, Shireesha; Kolli, Swathi; Shaik, Mahaboob V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Current study designed to identify the causes of abnormal uterine bleeding( AUB) in perimenopausal women and also to correlate with their histopathological examination. Methods: A prospective study of 65 perimenopausal women with complaint of AUB with age group ranging from 40 to 1 year within menopause those are attending to department of gynaecology of Narayana Medical College & Hospital, Nellore. Clinical examinations between the parameters were analysed. Histopathological examination report was also correlated with clinical examination and ultrasonography. Results: Out of 65 women, 11 (16.9%) were primiparas, 36 (55.38%) were para 2, 18 (27.69%) were para 3 and above. The frequent menstrual abnormality seen in perimenopausal women is heavy menstrual bleeding i.e., 41 (63%) women out of 65 women, 14 (21.53%) had polymenorrhoea, 9 (13.84%) had oligomenorrhea, 6 (9.23%) had postmenopausal bleeding, 4 (6.15%) had intermenstrual spotting. Most common type of endometrial pattern is proliferative endometrium. Out of 65 perimenopausal women, 23 (35.38%) had proliferative type of endometrium, 20 (30.76%) women had secretory pattern, 9 (13.84%) had typical simple endometrial hyperplasia, 4 (6.15%) had atypical simple endometrial hyperplasia, 3 (4.61%) had adenomyomatous polyp, and 6 (9.2%) women had irregular ripening. Conclusions: The present study shows that Histopathological examination is mandatory in all cases of AUB in perimenopausal age. 66.14% had benign pathology which can be managed by hormonal therapy or conservative surgical modalities which alleviates need for unnecessary hysterectomy.